STUDI KETERSEDIAAN N-TANAH DI SENTRA TANAMAN BAWANG PUTIH (Allium sativum L.), KECAMATAN PUJON, MALANG, JAWA TIMUR - Ketriwani Panggabean; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Pujon District is one of garlic centers for increasing garlic production in Malang. One of the causes of low garlic production is the low soil fertility. The status of soil fertility in garlic areas is influenced by availability of soil N. This study was conducted in Pujon District, Malang. The observation points were spread over five villages of garlic centers, i.e. Pandesari, Pujon Lor, Sukomulyo, Bendosari, and Madiredo. Correlation analysis was conducted for data of soil chemical and physical properties obtained from laboratory analysis. The garlic production was used as a dependent variable, while the soil N-total, C-organic, pH (H2O), pH (KCl), bulk density, and soil porosity, were used as the independent variables. Results showed that status of soil N the garlic center of Pujon District was in the low to medium category. Content of N in the topsoil (0-30cm) of the five land mapping units was medium, while that in the subsoil (30-60cm) of the five land mapping units ranged from low to medium. The large or small N content in the soil did not significantly correlated to organic C, pH (H2O and KCl), bulk density and soil porosity. There was a significant correlation between garlic production and the C/N ratio. However, the significant correlation was only found in the lower layer (30-60cm) with the r=0.82**.